2016
DOI: 10.2320/matertrans.m2016131
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rhenium-Rich Particles at Grain Boundaries in Nickel-Base Superalloy Turbine Blades

Abstract: Ni-base single crystal superalloy turbine blades containing defect grains were investigated by high resolution electron microscopy. Several different types of defects, such as, stray grains, equiax grains and freckle chains which formed during casting, and recrystallized grains which formed during subsequent heat treatment, were selected. Regardless of the region of the turbine blade, many particles with large amounts of rhenium were detected at the boundary of the stray grain and matrix. The Re-rich particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…A magnified image of the cross section (Figure 2c) shows that there are several fine particles along the boundary regions of two grains which look like the same orientation of {001} of the γ' phase (exactly the misorientation of 7.1°). This observation is in good agreement with a previous study which showed a similar microstructure of the particles in a low-angle grain boundary of 6.1° [16].…”
Section: General Distribution and Morphology Of Rhenium-rich Particlessupporting
confidence: 93%
See 3 more Smart Citations
“…A magnified image of the cross section (Figure 2c) shows that there are several fine particles along the boundary regions of two grains which look like the same orientation of {001} of the γ' phase (exactly the misorientation of 7.1°). This observation is in good agreement with a previous study which showed a similar microstructure of the particles in a low-angle grain boundary of 6.1° [16].…”
Section: General Distribution and Morphology Of Rhenium-rich Particlessupporting
confidence: 93%
“…Then, for reference, a new turbine blade with a high-angle boundary with a misorientation of 16.5° was observed. As already shown in previous studies [16,17], at the high-angle grain boundary, the intermediate layer becomes wider and clearer (Figure 2g) and most of all, the fine particles are easily recognized along the coherent interface. It should be noted that for more clear visualization of the distribution of the particles, a cross section was made along the intermediate layer, as shown in Figure 2h, which is different from the directions in Figure 2b,e.…”
Section: General Distribution and Morphology Of Rhenium-rich Particlessupporting
confidence: 85%
See 2 more Smart Citations
“…This sharp interface has also been confirmed in many other samples and with grain defects across a range of causes both thermal and solutal such as other stray grains, multigrain regions, freckle chain grains, and even low angle grain boundary. [5] Therefore, it is apparent that bi-films themselves did not exist in the samples examined in this and other studies.…”
mentioning
confidence: 91%